COLLECTION AND EXTRACTION OF ANDIROBA OIL (CARAPA GUIANENSIS) IN THE VILLAGE OF FORTALEZINHA (MARACANÃ, PARÁ): RIVERINE EXTRACTORS' PRACTICE AND POPULAR KNOWLEDGE (Editora Impacto Científico, 2025)
Andiroba (Carapa guianensis Aubl.) is a native species of the Amazon, belonging to the Meliaceae family, found throughout Latin America, across the Amazon Basin, in Africa, and south of the Sahara. It mainly grows in floodplain areas, floodable zones, and on dry land. Studies show that the seed oil of andiroba has unique properties with great therapeutic potential, being one of the most sold medicinal products in the Amazon and widely used by traditional populations.In this study, conducted from June to September 2024, the artisanal extraction process of andiroba oil and the techniques used by local riverine communities in the village of Fortalezinha, Maracanã, Pará, were recorded and described. Interviews with four harvesters and oil extractors were carried out using audiovisual recordings, where they shared how they perform the process, its purpose, and the importance of maintaining this traditional practice.The extraction process involved collecting the nuts, cooking, extracting the pulp, and then extracting the oil, taking approximately 50 days in total. Similarities were observed in the accounts regarding the steps and the uses of the oil. According to the extractors, the amount of oil and seeds collected during the research year was lower than in previous years, raising concerns that may be directly related to climate change. Systematic monitoring and recording of traditional practices are extremely important, not only to preserve this knowledge but also as a relevant indicator of environmental changes observed by the community, which has a close relationship with nature.DOI: https://doi.org/10.56238/edimpacto2025.090-078